Antifungal Pharmacotherapy and Hepatic Safety: Mechanisms of Drug-Induced Liver Injury (DILI) and Risk Mitigation - Sharma, Vadisha; Kaur, Navjot; Sharma, Rahul Kumar (Scripta Medica, 2026)
The growing prevalence of invasive fungal infections (IFIs), especially among immunocompromised patients, has resulted in increased reliance on systemic antifungal therapies. Hepatotoxicity is still a serious clinical problem even with improvements in treatment results. This study consolidates the mechanisms, incidence rates and risk factors associated with drug-induced liver injury (DILI) across various antifungal classes, including flucytosine, azoles, polyenes, echinocandins and allylamines. Triazole antifungals, such as voriconazole, fluconazole and ketoconazole are particularly implicated because of their substantial hepatic metabolism via cytochrome P450 enzymes and potential for interactions between drugs. Direct hepatocyte damage, immune-mediated responses, mitochondrial malfunction and changes in cytokine signalling are some of the mechanisms of hepatotoxicity. Terbinafine and other echinocandins and allylamines can also be hepatotoxic, particularly when combined with polypharmacy and pre-existing liver illness. Acute liver failure and asymptomatic liver enzyme increases are examples of clinical symptoms. To maximise treatment while reducing hepatic side effects, a thorough understanding of antifungal pharmacokinetics, metabolism and patient-related risk factors is necessary.
Keywords: Antifungal agents; Drug-induced liver injury; Hepatotoxicity; Polypharmacy; Triazoles